Evidence for H2 consumption by uncultured Desulfobacterales in coastal sediments. (14th September 2017) - Dyksma, Stefan; Pjevac, Petra; Ovanesov, Kin; Mussmann, Marc
Summary: Molecular hydrogen (H2 ) is the key intermediate in the anaerobic degradation of organic matter. Its removal by H2 ‐oxidizing microorganisms is essential to keep anaerobic degradation energetically favourable. Sulfate‐reducing microorganisms (SRM) are known as the main H2 scavengers in anoxic marine sediments. Although the community of marine SRM has been extensively studied, those consuming H2 in situ are completely unknown. We combined metagenomics, PCR‐based clone libraries, single‐amplified genomes (SAGs) and metatranscriptomics to identify potentially H2 ‐consuming SRM in anoxic coastal sediments. The vast majority of SRM‐related H2 ase sequences were assigned to group 1b and 1c [NiFe]‐H2 ases of the deltaproteobacterial order Desulfobacterales . Surprisingly, the same sequence types were similarly highly expressed in spring and summer, suggesting that these are stable and integral members of the H2 ‐consuming community. Notably, one sequence cluster from the SRM group 1 consistently accounted for around half of all [NiFe]‐H2 ase transcripts. Using SAGs, we could link this cluster with the 16S rRNA genes of the uncultured Sva0081‐group of the family Desulfobacteraceae . Sequencing of 16S rRNA gene amplicons and H2 ase gene libraries suggested consistently high in situ abundance of the Sva0081 group also in other marine sediments. Together with other Desulfobacterales these likely are important H2 ‐scavengers in marine sediments.